2020
DOI: 10.1016/j.respol.2020.104051
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the equity gap for young innovative companies: The design of effective government venture capital fund programs

Abstract: Governmental venture capital funds (GVCs) are created by policymakers around the world to support young innovative companies (YICs) with the aim of "bridging the equity gap". In this paper, we study the heterogeneity in the design of GVC programs in Europe and identify the design features that are most effective in achieving the desired outcomes of this policy. Specifically, we focus on the probability that GVC-backed companies will receive additional funds from private venture capital investors and, ultimatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 91 publications
(132 reference statements)
0
35
0
3
Order By: Relevance
“…Anesco and Petainer) have thrived, with a small proportion of stellar outliers generating substantial net new jobs, wealth and innovation spillovers, supporting the case for GVCFs [44], [26], [51]. Various commentators [44], [30], [7], [53], [56], [57], [58], [59], find that private VC funds are a well-established source of risk finance. VC fund managers, acting as expert financial intermediaries [44], [2], [57], have the ability to use their track records to raise substantial funds from large private institutional investors (e.g.…”
Section: The Role Of Gvcf In the Uk Early-stage Cleantech Finance Marketmentioning
confidence: 93%
See 2 more Smart Citations
“…Anesco and Petainer) have thrived, with a small proportion of stellar outliers generating substantial net new jobs, wealth and innovation spillovers, supporting the case for GVCFs [44], [26], [51]. Various commentators [44], [30], [7], [53], [56], [57], [58], [59], find that private VC funds are a well-established source of risk finance. VC fund managers, acting as expert financial intermediaries [44], [2], [57], have the ability to use their track records to raise substantial funds from large private institutional investors (e.g.…”
Section: The Role Of Gvcf In the Uk Early-stage Cleantech Finance Marketmentioning
confidence: 93%
“…GVCFs have been highly criticized for underperformance, particularly when compared to private VC investment exit returns (e.g. [7], [8], [21], [12], [28], [65], [66], [67], [68]). However, others [8], [26], argue that the older vintage of GVCFs required to analyze exit outcomes are outmoded program designs.…”
Section: The Role Of Gvcf In the Uk Early-stage Cleantech Finance Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…A relieving message comes the from studies that found that an increase in any of the market sides leads to an increase in the other side [18,19]. Additionally, there are many recommendations from the researchers on how particular policies have to be improved [41,42]. Nevertheless, researchers have acknowledged that government VC support schemes for a particular side of the market could not be viewed in isolation [29,43], and there is a necessity to create complementary policies.…”
Section: How Can a Country Activate Vc Market?mentioning
confidence: 99%
“…Even though this phenomenon was originally discussed in the context of the loan market, it also affects the supply of equity. [2] There are three main sources of financing SMEs. The first is venture capital, which came in addition to the second source -lending, and also digital finance, which has begun to gain popularity in recent years.…”
Section: Introductionmentioning
confidence: 99%